STUDYING THE EFFECT OF MAGNETIC FLUX ON DIESEL FUEL LINE ON SOME PERFORMANCE AND EMISSION OF DIESEL ENGINE - M. J. Mohammed,; N. S. Kadhim,; N. J. Imran, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to investigation was carried out to evaluate the performance and product emission of four cylinder 4- stroke water cooled  direct injection (DI) diesel engine fueled by permanent magnet exposed diesel fuel compared with diesel fuel (DF). Three levels of magnet field intensity were used including  Diesel fuel exposer to 3000 Gauss (DG3), Diesel fuel exposer to 5000 Gauss (DG5) and Diesel fuel exposer to 9000 Gauss (DG9)  fuel respectively. Permanent magnetic device was employed and installed on fuel line before interring high pressure fuel injection pump . The engine run at constant speed 1500rpm(revolution per minute) and loaded by two levels 4.5 kW and 9 kW represented as L1and L2 respectively. Results obtained showed that fuel DG5 registered an increased in thermal efficiency(TE) about 20.09% at load L1 compared with DF. Maximum reduction in brake specific fuel consumption (bsfc) about 12.12%, when using DG5 fuel at load 1 compared to DF fuel. All exhaust emission Unburned Hydrocarbon (UHC), Carbon Monoxide (CO), Carbon Dioxide (CO2),Particular Maters (PM), and Nitrogen Oxides (NOx) are decreased when diesel fuel treated with different magnetic intensities 3000,5000 and 9000 Gauss. Compared with conventional diesel fuel. Maximum reduction in PM,HC,NOx,CO2,and CO about 16.56-27.08%, 3.89–64.26%, 4.79–7.91%, 4.05-5.71and 11.46-53.48% respectively. CO2 emission was increased by 1.65-4.28 at DG5 with L1 and L2 respectively due to the operating conditions.